INOVASI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY( ICT) - Rizki Inayah Putri; Harmin Hatta; Zainal Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
This study aims to describe ICT-based learning media, visual intelligence, Islamic Religious Education, and innovation of ICT-based learning media towards visual intelligence in Islamic Religious Education. This article is also expected to contribute to the world of education and also to further relevant researchers. This study uses library research. Research sources are obtained from various scientific sources, namely books, journal articles, and various other sources related to research studies. The use of learning media for students must first require educators to know the characteristics of their students, including students who have visual intelligence. Educators must adjust the learning style of these students which tends to refer to the intelligence that students have. Educators can apply learning media by entering the world of students. Entering the world of students in question is that educators in delivering material adjust their teaching style to the learning style of their students. Educators can utilize Microsoft Powerpoint and Lectora Inspire which can present images and abstract materials to be more concrete in front of students, such as text represented by images on their slides. Educators can utilize videos to present moving images that are able to present actual objects with the original spatial layout of the object or duplicate the actual object, such as animated videos.